2013
DOI: 10.1111/cen.12371
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges of serum TSH, FT4 and thyroid autoantibodies in the Thai population: the national health examination survey

Abstract: The reference interval for TSH needs to be derived from each specific population. Slightly elevated TSH concentrations in the elderly could be considered acceptable, with no need for thyroxine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
4
26
2
Order By: Relevance
“…We speculated with caution that apparently thyroid healthy individuals were likely to be recruited without rigorous exclusion criteria and iodine nutritional status was also not considered when the manufactures established the RIs of thyroid hormones. Table 4 shows the RIs of thyroid hormones reported by the investigators in various countries and regions during the past decade [11][12][13][16][17][18][19][20][21][22]. Our upper-limit of serum TSH level was marginally higher than Guan's results but similar with Li's results [11,13].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We speculated with caution that apparently thyroid healthy individuals were likely to be recruited without rigorous exclusion criteria and iodine nutritional status was also not considered when the manufactures established the RIs of thyroid hormones. Table 4 shows the RIs of thyroid hormones reported by the investigators in various countries and regions during the past decade [11][12][13][16][17][18][19][20][21][22]. Our upper-limit of serum TSH level was marginally higher than Guan's results but similar with Li's results [11,13].…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that significant differences among all the age groups were observed in FT 3 , but neither in TSH nor in FT 4 . The findings were in accord with substantial previous studies [12,21,22,24,25], but were inconsistent with several other studies [13,17,20]. The possible explanations might be associated with the differences of race and iodine nutritional status [17,24,26,27].…”
Section: The Effects Of Age and Gender On Tsh And Other Thyroid Hormocontrasting
confidence: 57%
“…That debate is related to the heterogeneity in TSH reference ranges established in previous studies (6,7,8,9,10,11,12,13) with differences of the upper TSH limit between 2.12 mIU/l (12) and 5.30 mIU/l (13). These discrepancies can be explained by different study populations, age ranges (4), laboratory methods (14), and iodine supplies of populations (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies can be explained by different study populations, age ranges (4), laboratory methods (14), and iodine supplies of populations (15,16). In regions with iodine deficiency, reference intervals for serum TSH levels tend to be lower than that in regions with sufficient iodine supply, leading to higher reference intervals in North America (6) and East Asia (8,10,13) than that in large parts of Europe (7,9,12), where most countries are inherently iodine deficient (17).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid autoantibodies might probably be markers of some other autoimmune disorder affecting the brain 4. The presence of antithyroperoxidase can be found in nearly 9% of the general Thai population,16 therefore, presence of high titres are necessary for the diagnosis of HE, but not specific. A recent report showed that serum autoantibodies against the N-terminal of α-enolase are a useful diagnostic biomarker for HE 17…”
Section: Discussionmentioning
confidence: 99%